Implementation of Jean Watson's Caring Theory in an Anti-Bullying Program for School Children's Psychosocial Development - Alicia Julyanti Malimbong; Arman Abdullah; Farija A Rahim; Azara Tri Hapsari; Lisa Amelia; Indra Dewi (Jurnal Abmas Negeri (JAGRI), 2026)
Bullying in elementary schools is a serious issue that negatively affects children’s psychosocial development, highlighting the need for holistic and sustainable prevention approaches. This community service activity aimed to examine the implementation of Jean Watson’s Caring Theory on the psychosocial development of school-aged children through an anti-bullying program at SD Negeri Tamalanrea, Makassar City, involving 50 students with active participation and teachers as supporting partners. The program employed an educational and participatory approach conducted through stages of problem identification, delivery of caring-based anti-bullying education, mentoring in the application of caring behaviors in the school environment, and program evaluation. Educational activities were delivered through interactive lectures, group discussions, educational games, and simple simulations tailored to the characteristics of school-aged children. The results showed improved students’ understanding of bullying, enhanced empathy and mutual respect, and better social interactions among students. The implementation of Jean Watson’s Caring Theory contributed positively to creating a safe, supportive, and inclusive school environment and to optimizing the psychosocial development of school-aged children.